Relationships between school support, school facilities, ICT culture and mathematics teachers' attitudes towards ICT in teaching and learning - Mohd Ayub, Ahmad Fauzi; Abu Bakar, Kamariah; Ismail, Rohayati (American Institute of Physics, 2011)
Information communication Technology (ICT) has been a major influence in the Malaysian Education System, especially in the teaching of mathematics. Since 2003, the Malaysian Ministry of Education has provided incentives to mathematics teacher to motivate them to use ICT using English as the medium of instruction, during the teaching and learning process. However, there are barriers that prevented mathematics teachers from using ICT in the classrooms. This study is to determine factors that influenced the attitudes of Malaysian Mathematic Teachers in integrating ICT in their teaching and learning. One hundred ninety one mathematics teachers were randomly selected for the purpose of this study. The three factors investigated were school support, school facilities and school culture which had been selected to be correlated with teachers’ attitudes towards integrating ICT in the teaching and learning of mathematics. Findings showed that significant positive relationships existed between teachers’ attitudes toward integrating ICT in the teaching and learning and school support, school facilities and ICT culture and This finding indicated that, in order to develop teachers’ attitudes in using ICT during their teaching and learning process, they needed support from the school principals and also their colleagues. Apart from that, school facilities and also ICT culture were also found to be essential.